2014
DOI: 10.1111/1469-0691.12562
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Middle East respiratory syndrome coronavirus infection in hospital patients and their healthcare worker and family contacts: a prospective descriptive study

Abstract: The Saudi Arabian Ministry of Health implemented a pro-active surveillance programme for Middle East respiratory syndrome (MERS) coronavirus (MERS-CoV). We report MERS-CoV data from 5065 Kingdom of Saudi Arabia individuals who were screened for MERS-CoV over a 12-month period. From 1 October 2012 to 30 September 2013, demographic and clinical data were prospectively collected from all laboratory forms received at the Saudi Arabian Virology reference laboratory. Data were analysed by referral type, age, gender,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
160
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(168 citation statements)
references
References 18 publications
(30 reference statements)
4
160
4
Order By: Relevance
“…Upper respiratory symptoms developed among 27% of case-contact compared to 33% of non-case-contacts [58]. Of the 48 case-contact, 87.5% had surgical mask and 33% had N-95 mask [58]. Contact investigation of healthcare workers (HCWs) of MERSCoV patients also revealed no transmission in two other studies [59,60].…”
Section: Transmission Of Mers-cov Among Family Contactsmentioning
confidence: 89%
See 2 more Smart Citations
“…Upper respiratory symptoms developed among 27% of case-contact compared to 33% of non-case-contacts [58]. Of the 48 case-contact, 87.5% had surgical mask and 33% had N-95 mask [58]. Contact investigation of healthcare workers (HCWs) of MERSCoV patients also revealed no transmission in two other studies [59,60].…”
Section: Transmission Of Mers-cov Among Family Contactsmentioning
confidence: 89%
“…Studies of the transmission of MERS-CoV in healthcare setting revealed a low transmission rate. The investigation of healthcare worker contacts of the first MERS case in KSA showed that none of the 48 case-contact and 48 non casecontacts was positive for MERS-CoV by HKU5.2N nucleocapsid enzyme immunoassay [58]. Upper respiratory symptoms developed among 27% of case-contact compared to 33% of non-case-contacts [58].…”
Section: Transmission Of Mers-cov Among Family Contactsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] The clinical sickness related to MERS-CoV ranges from mild upper respiratory manifestations to fulminant pneumonia and multi-system failure. [4,5,6] Human-tohuman transmission of MERS-CoV is all around recorded in the family, group settings and more frequently in social insurance settings [4,7,8]. As such, bigger hospital outbreaks have been driven by a combination of overdue recognition, over-crowding, and inadequate infection control precautionary measures [6,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is also clear that patients without underlying diseases can become infected, although most develop asymptomatic or mild clinical disease 52, 74,75 . MERS-CoV transmission requires close contact between infected patients and susceptible individuals, but even under these conditions, only a limited amount of transmission has been documented 52, [74][75][76][77] . In one study, Drosten et al showed that the rate of transmission from 26 MERS patients to 280 household contacts was approximately 4% 52 .…”
Section: Human To Human Transmissionmentioning
confidence: 99%